Efficacy of Biological-Targeted Treatments in Takayasu Arteritis: Multicenter, Retrospective Study of 49 Patients. Issue 18 (3rd November 2015) - Mekinian, Arsene; Comarmond, Cloé; Resche-Rigon, Mathieu; Mirault, Tristan; Kahn, Jean Emmanuel; Lambert, Marc; Sibilia, Jean; Néel, Antoine; Cohen, Pascal; Hie, Miguel; Berthier, Sabine; Marie, Isabelle; et al.
Abstract : Background—: The goal of this work was to assess the safety and efficacy of biologics (ie, tumor necrosis factor-α antagonists and tocilizumab) in patients with Takayasu arteritis. Methods and Results—: This was a retrospective, multicenter study of the characteristics and outcomes of 49 patients with Takayasu arteritis (80% female; median age, 42 years [20–55 years] treated by tumor necrosis factor-α antagonists [80%] or tocilizumab [20%]) and fulfilling American College of Rheumatology or Ishikawa criteria. Factors associated with complete response were assessed. Eighty-eight percent of patients with Takayasu arteritis were inadequately controlled with or were intolerant to conventional immunosuppressive therapy (median number, 3 [1–5]). Overall response (ie, complete and partial) to biological-targeted treatments at 6 and 12 months was 75% and 83%, respectively. There were significantly lower C-reactive protein levels at the initiation of biological-targeted treatments (22 mg/L [10–46 mg/L] versus 58 mg/L [26–76 mg/L]; P =0.006) and a trend toward fewer immunosuppressants drugs used before biologics ( P =0.054) in responders (ie, complete or partial responders) relative to nonresponders to biological-targeted treatments. C-reactive protein levels and daily prednisone dose significantly decreased after 12 months of biological-targeted treatments (30 versus 6 mg/L [ P <0.05] and 15 versus 7.5 mg [ P <0.05] at baseline and 12 months, respectively). The 3-year relapse-free survival was 90.9% (83.5%–99%) over the biological treatment period compared with 58.7% (43.3%–79.7%; P =0.0025) with disease-modifying antirheumatic drugs. No difference in efficacy was found between tumor necrosis factor-α antagonists and tocilizumab. After a median follow-up of 24 months (2–95 months), 21% of patients experienced adverse effects, with biological-targeted treatments discontinued in 6.6% of cases. Conclusion—: This nationwide study shows a high efficacy of biological-targeted treatments in refractory patients with Takayasu arteritis with an acceptable safety profile.